Pemanfaatan Limbah Batang Pisang Menjadi Keripik Desa Mamampang, Kabupaten Bantaeng - ., Nuraksa; Setiawan, Irwan; F, Andi Syahreza; Feryanto, Wahyu; Cahyani, Rani; M, Weney Kanatya; Fadillah, Nur; F, Widya Ananda (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The improvement of Science and Technology (IPTEK) in all aspects of Economy, Culture and Education is very important. One of the efforts made by the students of KKN (Real Work Lecture) Thematic 112 Mamampang Village to increase public awareness in utilizing materials that can be used to increase income and creativity of the community. Mamampang Village is a very strategic village, 7 km south of the capital of Bantaeng Regency and directly borders Eremerasa District (Ulugalung Village). The most of the Mamampang village area is rice fields and plantations, which means it is one of the productive areas producing rice and corn, bananas in Bantaeng Regency. Banana stems have porous, hollow, and fibrous characteristics so that their density value is high. In addition, banana stems have a cellulose content of more than 50%. The goals and benefits of processing banana stems include the production of food and beverages such as banana stem juice and banana stem chips, which contribute to improving the community's economy. This processing helps reduce waste and encourages the use of sustainable natural resources in the village. The training and socialization methods carried out by Hasanuddin University KKN students to process banana stems into juice, banana stems into chips, the results showed an increase in knowledge of the use of banana stems into chips by 88%, which initially only 5% understood this. Finally, participants understand the use of banana stems to make chips and it will immediately accelerate the formation of women's groups (PBP2D) for production and marketing, increasing knowledge and economic opportunities for the community.